Moxidectin Efficacy in a Goat Herd with Chronic and Generalized Sarcoptic Mange - Nektarios D. Giadinis; Rania Farmaki; Nikolaos Papaioannou; Elias Papadopoulos; Harilaos Karatzias; Alexander F. Koutinas (Veterinary Medicine International)
A case of sarcoptic mange affecting almost all the animals of a dairy goat herd is described. This pruritic skin disease led progressively to high mortality and dramatic drop of milk yield. The lesions of the affected goats were typical of a chronic and generalized-diffuse sarcoptic mange. Diagnosis was confirmed by skin scrapings and histopathology in which many mites were demonstrated. All surviving goats were treated with injectable moxidectin solution 1% (CYDECTIN-Fort Dodge) at the dose of 0.2 mg/kg, applied every 15 days for four times, subcutaneously. Although pruritus had decreased soon after the first treatment, a satisfactory healing of cutaneous lesions was witnessed 6 weeks after the beginning of moxidectin trial. Parasitological cure was achieved in all affected animals by the end of the trial. In the four monthly followups, no evidence of sarcoptic mange could be found.